Projectile wireless setting and Mechanical testing technology. Issue 1 (July 2021) - Zhang, Mingyue; Fang, Liqing; Shi, Yonglei
Abstract: This paper discusses the mechanical testing technology used in the wireless setting system of projectile, mainly including sensor, signal processing, system analysis, error analysis and data processing theory. The circuit simulation and system analysis are carried out by using Multisum, and the magnetic field simulation is carried out by using CST. The wireless setting scheme based on electromagnetic induction is designed, and the scheme is analyzed and improved. Finally, the data of range and firing angle of the projectile in high-speed motion can be set quickly.